Biological Relationships between Foragers and Farmers of South-Central North America: Nonmetric Dental Traits. Issue 1 (20th January 2012) - Taylor, Matthew; Creel, Darrell
Abstract: Studies of relationships between archeology and biology in the south-central North America can enhance interpretations of social interactions between foraging and farming groups. The present report analyzes the adult dentition of hunter-gatherer populations from what is now Texas and compares them with adjacent samples of agriculturalists. These agriculturallist samples represent the Southwestern (Mimbres-Mogollon) and Southeastern (Caddo) cultural spheres. Nonmetric dental traits provide a useful means for evaluating the biological similarities between different populations. Mahalanobis distance analysis of these traits, drawn from 902 individuals, reveal relatively little morphological similarity between hunter-gatherer and farming groups. Except for a sample of Archaic foragers from the gulf coastal plain, hunter-gatherer samples are more similar to each other than to adjacent agriculturalists. Results suggest that Archaic populations were morphologically diverse, while there was relatively little gene flow between hunter-gatherer and farming populations during the Late Prehistoric period. The overall dissimilarity between hunter-gatherer, Mimbres, and Caddo samples suggests that each may have arisen from a relatively distant common ancestry.